Heme Biosynthetic Pathway is Functionally Linked to Adipogenesis via Mitochondrial Respiratory Activity. Issue 10 (31st August 2017) - Moreno‐Navarrete, José María; Rodríguez, Amaia; Ortega, Francisco; Becerril, Sara; Girones, Jordi; Sabater‐Masdeu, Mònica; Latorre, Jéssica; Ricart, Wifredo; Frühbeck, Gema; Fernández‐Real, José Manuel
Abstract : Objective: To investigate key enzymes of heme biosynthesis in human adipocytes and adipose tissue (AT). Methods: Heme biosynthesis‐related gene expression ( ALAS1, ALAD, HMBS ) was investigated in whole AT from humans ( n = 178 and n = 75) and rats according to obesity status and during adipogenesis of human preadipocytes. The effects of aminotriazole (an ALAD inhibitor) and of ALAD knockdown were also studied. Results: Consistent heme biosynthesis‐related gene expression was detected in both subcutaneous AT (SAT) and visceral AT (VAT) and was significantly increased in SAT. ALAS1, ALAD, and HMBS mRNAs were positively associated with adipogenic gene expression in human AT and significantly decreased in subjects with obesity. These results were replicated in an independent cohort. Both SAT and VAT heme levels were positively correlated with ALAS1, ALAD, and HMBS mRNAs. ALAD and HMBS were mainly expressed in adipocytes and increased during differentiation of human adipocytes in parallel to adipogenic genes. In rats, high‐fat diet‐induced weight gain resulted in decreased Alad and Hmbs mRNAs in a similar way to what was observed with Adipoq . Aminotriazole administration or ALAD knockdown attenuated adipogenesis in parallel with decreased glucose uptake and impaired mitochondrial respiratory function during human adipocyte differentiation. Conclusions: Current data suggest a possible role of heme biosynthesis in human adipogenesis.